2015
DOI: 10.1037/abn0000071
|View full text |Cite
|
Sign up to set email alerts
|

Local area disadvantage and gambling involvement and disorder: Evidence for gene-environment correlation and interaction.

Abstract: Previous research has demonstrated that local area characteristics (such as disadvantage and gambling outlet density) and genetic risk factors are associated with gambling involvement and disordered gambling. These two lines of research were brought together in the present study by examining the extent to which genetic contributions to individual differences in gambling involvement and disorder contributed to being exposed to, and were also accentuated by, local area disadvantage. Participants were members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…All in all, the key finding of our study is that lower‐income individuals contribute proportionally more of their income to gambling compared to middle‐ and high‐income groups . It is noteworthy that people who are already in precarious social and financial situations tend to live in neighbourhoods with a high density of gambling opportunities . The associated risk of gambling‐related problems and experienced harms gives rise to inequality, as pointed out by Selin and colleagues .…”
Section: Discussionsupporting
confidence: 53%
“…All in all, the key finding of our study is that lower‐income individuals contribute proportionally more of their income to gambling compared to middle‐ and high‐income groups . It is noteworthy that people who are already in precarious social and financial situations tend to live in neighbourhoods with a high density of gambling opportunities . The associated risk of gambling‐related problems and experienced harms gives rise to inequality, as pointed out by Selin and colleagues .…”
Section: Discussionsupporting
confidence: 53%
“…It is equally plausible that these might reflect the impact of the individual on her choice of environment (Gruenewald, ); this might be especially germane to young adults just beginning to exert their independence. The impact of the individual is nicely illustrated by a recent twin study that found that individual differences in moving to or remaining in a disadvantaged neighborhood was due in part to genetic factors (Slutske et al., ). Only a handful of studies have been able to disentangle the potentially causal influences of the alcohol environment from selection into such an environment (Buu et al., ; Jokela, ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found availability of gambling outlets to lead to increased gambling addiction (4446). Since a hallmark of addiction is continued use despite negative consequences, the lack of subsequently impaired function is one way to distinguish between healthy and unhealthy use.…”
Section: Discussionmentioning
confidence: 99%